Dose-Dependent Microglial and Astrocytic Responses Associated With Post-ischemic Neuroprotection After Lipopolysaccharide-Induced Sepsis-Like State in Mice - Sardari, Maryam; Dzyubenko, Egor; Schmermund, Ben; Yin, Dongpei; Qi, Yachao; Kleinschnitz, Christoph; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2020)
In contrast to lipopolysaccharide (LPS)-induced preconditioning, which has repeatedly been examined in the past, the effects of post-ischemic LPS-induced sepsis, although clinically considerably more important, have not systemically been studied. We exposed mice to transient intraluminal middle cerebral artery occlusion and examined the effects of intraperitoneal LPS (0.1 or 1 mg/kg) which was administered 24 hours post ischemia. Post-ischemic glial reactivity, neuronal survival and neurological outcome were differently modulated by the higher and the lower LPS dose. Although both doses promoted neuronal survival after 72 hours, the underlying mechanisms were not similar. Mice receiving 1 mg/kg LPS exhibited transient hypothermia at 1 and 3 hours post sepsis (hps), followed by reduced focal neurological deficits at 24, 48 and 72 hps. The lower dose (0.1 mg/kg) did not induce hypothermia, but reduced microglia/macrophage activation with appearance of an anti-inflammatory CD206 positive cell phenotype in the brain parenchyma. Together, our results indicate a novel, dose-dependent modulation of microglial cells that is intricately involved in brain protection.